Pharmacological Treatments and Natural Biocompounds in Weight Management - Amin Gasmi; Pavan Kumar Mujawdiya; Amine Nehaoua; Mariia Shanaida; Yuliya Semenova; Salva Piscopo; Alain Menzel; Volodymyr Voloshyn; Olena Voloshyn; Volodymyr Shanaida; Geir Bjørklund (MDPI AG, 2023)
The obesity pandemic is one of society's most urgent public health concerns. One-third of the global adult population may fall under obese or overweight by 2025, suggesting a rising demand for medical care and an exorbitant cost of healthcare expenditure in the coming years. Generally, the treatment strategy for obese patients is largely patient-centric and needs dietary, behavioral, pharmacological, and sometimes even surgical interventions. Given that obesity cases are rising in adults and children and lifestyle modifications have failed to produce the desired results, the need for medical therapy adjunct to lifestyle modifications is vital for better managing obesity. Most existing or past drugs for obesity treatment target satiety or monoamine pathways and induce a feeling of fullness in patients, while drugs such as orlistat are targeted against intestinal lipases. However, many medications targeted against neurotransmitters showed adverse events in patients, thus being withdrawn from the market. Alternatively, the combination of some drugs has been successfully tested in obesity management. However, the demand for novel, safer, and more efficacious pharmaceutical medicines for weight management does exist. The present review elucidates the current understanding of the available anti-obesity medicines of synthetic and natural origin, their main mechanisms of action, and the shortcomings associated with current weight management drugs.